2011
DOI: 10.1155/2011/874146
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Vascular Complications in the JAK2 V617F-Positive Myeloproliferative Neoplasms

Abstract: We previously found that gender influenced the JAK2 V617F allele burden, but it is unknown whether this gender difference in molecular epidemiology influences complications in the myeloproliferative neoplasms (MPNs). Historically, vascular complications represented the most common cause of mortality in polycythemia vera and essential thrombocytosis and contributed to morbidity in primary myelofibrosis. To determine the influence of gender on vascular complications, we retrospectively analyzed associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…Consistent with the phenotypic and genotypic differences between male and female PV patients [31][32][33][34], there are different miRNA deregulations between male and female patients (Fig. 1).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with the phenotypic and genotypic differences between male and female PV patients [31][32][33][34], there are different miRNA deregulations between male and female patients (Fig. 1).…”
Section: Discussionsupporting
confidence: 75%
“…Since erythrocytosis is the only feature that distinguishes PV from ET, we also compared specific miRNA expression in the nucleated erythroid cells directly descended from the burstforming unit erythroid (BFU-E) progenitor cells of PV and ET patients. Our data indicate that significant miRNA deregulation occurs in the CD34+ cells of PV patients and confirm a genetic basis for the gender-specific differences that characterize PV [31][32][33][34]. The results of our study also suggest that deregulated miRNAs may represent an important mechanism by which the PV erythrocytosis and ET thrombocytosis phenotypes are determined.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with previous findings, with published data historically supporting a prevalence of females among ET patients and a prevalence of males among patients with PV. [13][14][15][16][17] Gender discrepancies within hematologic malignancies are not unique to MPN. Similar discordances in gender prevalence have been demonstrated in other disorders such as acute lymphoblastic leukemia, chronic lympho-…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation identified that women were more likely to experience macrothrombosis within the abdominal venous system (hepatic, portal, mesenteric or splenic veins) whereas males were more likely to experience events in the deep venous system, including limb thrombosis and pulmonary emboli. 16 Although the influence of gender on the pathogenesis of thrombosis remains unclear, mounting evidence suggests that both the type and ratio of circulating sex hormones plays an important role in the thrombotic cascade. In an investigation involving exogenous sex-steroid administration, ET patients exposed to hormone replacement therapy (estrogen only) had similar rates of arterial and venous thrombosis when compared to ET patients not on therapy.…”
mentioning
confidence: 99%